2020
DOI: 10.48550/arxiv.2011.07105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reinforcement Learning Control of a Biomechanical Model of the Upper Extremity

Florian Fischer,
Miroslav Bachinski,
Markus Klar
et al.

Abstract: We address the question whether the assumptions of signal-dependent and constant motor noise in a full skeletal model of the human upper extremity, together with the objective of movement time minimization, can predict reaching movements. We learn a control policy using a motor babbling approach based on reinforcement learning, using aimed movements of the tip of the right index finger towards randomly placed 3D targets of varying size. The reward signal is the negative time to reach the target, implying movem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…They do not make particular a priori assumptions about the structure of the cost function. Instead, they use an inverse optimal control approach to fit a generic function with a large number of parameters (36) to a dataset of mouse pointer movements. While Ziebart et al [145] focus on the application of inverse optimal control to pointing target prediction, in this paper we investigate the ability of optimal (feedback) control models to model movement of the mouse pointer more quantitatively.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…They do not make particular a priori assumptions about the structure of the cost function. Instead, they use an inverse optimal control approach to fit a generic function with a large number of parameters (36) to a dataset of mouse pointer movements. While Ziebart et al [145] focus on the application of inverse optimal control to pointing target prediction, in this paper we investigate the ability of optimal (feedback) control models to model movement of the mouse pointer more quantitatively.…”
Section: Related Workmentioning
confidence: 99%
“…Cheema et al [24] have applied recent RL methods to predict fatigue during mid-air movements, using a torque-actuated linked-segment model of the upper limb. Building on this work, it has recently been shown that RL applied to a more realistic upper-limb model allows to synthesize human arm movements that follow both Fitts' Law and the 2 /3 Power Law and can predict human behavior in mid-air pointing and path following tasks [36]. Moreover, an extension to mid-air keyboard typing has been proposed [55].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, physics engines such as PyBullet [15], MuJoCo [16] and Dart [17] are relatively more efficient and support contact interactions but lack adequate support for muscle modeling (PyBullet and Dart) or lack functionally validated musculoskeletal models. Even though attempts have been made in adding physiological models in MuJoCo [18]- [20], they were limited in their validation.…”
Section: Introductionmentioning
confidence: 99%